ENSURING THE INVESTMENT ATTRACTIVENESS OF BUSINESS STRUCTURES DURING THE WAR AND POST-WAR PERIOD ON THE EXAMPLE OF THE PLANT «KHMELNYTSKZALIZOBETON» - TANASIENKO, Nataliia; VRUBLEVSKYI, Ivan; PYATNYCHKA, Vasyl; URIZCHENKO, Vadym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The aim of the research is to develop the strategic and tactical measures to increase the investment attractiveness of the enterprise and recommendations for improving the efficiency of its activities in the conditions of war and the post-war period on the example of the plant «Khmelnitskazizobeton».The plant «Khmelnitskzalizobeton» holds a leading position in the construction industry of Ukraine, focusing on the manufacture of products for housing and road construction, engineering and electrical infrastructure, as well as the production of concrete, mortar and joinery.The study analyses the dynamics of the key financial indicators of the plant «Khmelnitskazizobeton» for 2021-2023. Based on the financial indicators, an integral indicator of the investment attractiveness of the enterprise is calculated. Strategic and tactical measures to improve the investment attractiveness of the enterprise in the conditions of war and the post-war period are proposed.Strategic and tactical measures are important to increase the investment attractiveness of business structures, especially in the war and post-war period. The strategic approach helps to define long-term goals and priorities aimed at creating a stable investment environment, while tactical measures provide a prompt response to current business challenges and needs. Together, they form a comprehensive mechanism that helps to attract investment, support the functioning of enterprises in difficult conditions, and ensure their competitiveness during the recovery period.
Keywords: investment attractiveness; strategic measures; tactical measures; the plant «Khmelnytskzalizobeton»